A descriptive study of Bengali words - Dash, Niladri Sekhar (Cambridge ; New York : Cambridge University Press, 2015)
"Provides a solid empirical support for developing tools and systems for morphological analysis, morphological generation, lexical decomposition and lexical composition for Bengali language for machine learning and language teaching"--
Includes bibliographical references (pages 335-340) and indexes.
Keywords: Bengali language -- Morphology -- Data processing; Bengali language -- Morphology -- Study and teaching; Bengali language -- Lexicology -- Data processing; Bengali language -- Lexicology -- Study and teaching; Bengali language -- Grammar